Diagnostic value of cytological analysis of tumours and tumour-like lesions of the oral cavity in dogs and cats: A prospective study on 114 cases. Issue 2 (August 2015) - Bonfanti, U.; Bertazzolo, W.; Gracis, M.; Roccabianca, P.; Romanelli, G.; Palermo, G.; Zini, E.
Highlights Cytology was compared to histopathology for the diagnosis of masses of the oral cavity of dogs and cats. FNI in dogs showed the highest sensitivity and specificity for oral tumours. In cats all methods had high sensitivity and specificity for oral lesions. Cytology is appropriate to correctly diagnose lesions of the oral cavity in dogs and cats.